(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Migration economies have long been a crucial area of study. There is no doubt that labour migration affects a variety of factors, including employment, the labour market, rural development, social welfare, labour management, migrant networks, etc. Making effective labour market policies and inclusive economic growth policies requires a solid understanding of the labour force. examining how labour migration policies have changed over time and their impact on a country’s labour market and overall economic development. This study, which is focused on secondary data sources, used descriptive research. Books, newspapers, journals, articles, and governmental websites are used to collect secondary data. A careful review of the literature shows that migration has always been a significant factor in population growth and economic development. In search of better lifestyles, people have crossed national and international borders. The effects of labour migration on national development are examined in this essay. The trends, patterns, causes, and effects of labour migration at both the international and national levels are presented.